Light-enhanced bioaccumulation of molybdenum by nitrogen-deprived recombinant anoxygenic photosynthetic bacterium Rhodopseudomonas palustris. Issue 2 (1st February 2016) - Naito, Taki; Sachuronggui,; Ueki, Masayoshi; Maeda, Isamu
Abstract: As molybdenum (Mo) is an indispensable metal for plant nitrogen metabolisms, accumulation of dissolved Mo into bacterial cells may connect to the development of bacterial fertilizers that promote plant growth. In order to enhance Mo bioaccumulation, nitrogen removal and light illumination were examined in anoxygenic photosynthetic bacteria (APB) because APB possess Mo nitrogenase whose synthesis is strictly regulated by ammonium ion concentration. In addition, an APB, Rhodopseudomonas palustris, transformed with a gene encoding Mo-responsive transcriptional regulator ModE was constructed. Mo content was most markedly enhanced by the removal of ammonium ion from medium and light illumination while their effects on other metal contents were limited. Increases in contents of trace metals including Mo by the genetic modification were observed. Thus, these results demonstrated an effective way to enrich Mo in the bacterial cells by the culture conditions and genetic modification. Graphical abstract: : Mo content was specifically enhanced in N-deprived photosynthetic bacterium harboring a gene coding Mo-binding protein (FL, full-length; CT, Mo-binding domain; EV, vector).